Effectiveness of family-based weight management interventions in childhood obesity: an umbrella review protocol. (September 2016) - Chai, Li Kheng; Burrows, Tracy; May, Chris; Brain, Katherine; Wong See, Denise; Collins, Clare
Abstract : Review question/objective: The main objective of this umbrella review is to identify the effectiveness of family-based interventions that target overweight or obesity in children aged 18 years and under. The umbrella review intends to compare and summarize existing systematic reviews of experimental studies that address a range of family-based interventions for overweight children. Family-based is defined as the involvement of first- or second-degree relatives or carers who are cohabiting under one roof. 1 The second objective of this umbrella review is to identify strategies that are effective in improving children's body weight or body mass index (primary outcomes) and, where applicable, changes in child/family behavior, including dietary intake or physical activity. The review questions are as follows: What is the effectiveness of family-based behavioral or lifestyle weight management interventions for overweight children? What are the strategies or characteristics of effective interventions in combating child obesity?